Mucilage Polysaccharide Composition and Exudation in Maize From Contrasting Climatic Regions - Nazari, Meisam; Riebeling, Sophie; Banfield, Callum C.; Akale, Asegidew; Crosta, Margherita; Mason-Jones, Kyle; Dippold, Michaela A.; Ahmed, Mutez Ali (Frontiers in Plant Science, 2020)
Mucilage, a gelatinous substance comprising mostly polysaccharides, is exuded by maize nodal and underground root tips. Although mucilage provides several benefits for rhizosphere functions, studies on the variation in mucilage amounts and its polysaccharide composition between genotypes are still lacking. In this study, eight maize (Zea mays L.) genotypes from different globally distributed agroecological zones were grown under identical abiotic conditions in a randomized field experiment. Mucilage exudation amount, neutral sugars and uronic acids were quantified. Galactose (~39–42%), fucose (~22–30%), mannose (~11–14%), and arabinose (~8–11%) were the major neutral sugars in nodal root mucilage. Xylose (~1–4%) and glucose (~1–4%) occurred only in minor proportions. Glucuronic acid (~3–5%) was the only uronic acid detected. The polysaccharide composition differed significantly between maize genotypes. Mucilage exudation was 135% and 125% higher in the Indian (900 M Gold) and Kenyan (DH 02) genotypes than in the central European genotypes, respectively. Mucilage exudation was positively associated with the vapor pressure deficit of the genotypes’ agroecological zone. The results indicate that selection for environments with high vapor pressure deficit may favor higher mucilage exudation, possibly because mucilage can delay the onset of hydraulic failure during periods of high vapor pressure deficit. Genotypes from semi-arid climates might offer sources of genetic material for beneficial mucilage traits.